(untitled) (Fiep Bulletin - online, 2014)
The Rhythmic Gymnastics is one of the sports that are mixed with beautiful arts, in terms of movements, by means of questions of aesthetic nature, for the plasticity, the corporal expression, the narrow harmony with music and movement and for the stimulants challenges presented by the rope, arc, ball, maces and ribbon. The adolescence presents excellent visible and invisible alterations, it is, an important phase of transistion between infancy and the adult age, so considered by diverse authors. Fascinated by the rgour, degree of difficulty and precision of the movements demanded in the competitions, athletes of this esportiva modality of sport and dedicate almost exclusively to its practise, which may harm the development. It fits here to stand out that this a sporting activity with competitive objectives brings benefits to the participant, but, it is also important to consider the possible damages responsibly. Based in the fhenomenological method and operations in the reflection description-axiológic reflection and dialectic, what was intended in this study was to lead through a reflection on the difficulty on presenting a matur development of adjusted psychosocial nature in the age understood between 12 and 16 years, in practicing adolescent athletes of rhythmic gymnastics, and thus, discovering solutions that minimize the observed problem.